일상생활요인이 노인의 삶의 만족도에 미치는 영향 - 리해근(Hae-Gun Rhee); 하규수(Kyu-Soo Ha) (한국콘텐츠학회 논문지, 12(6), 2012)
In this study, I tried to find out the effect of the daily living factors(social support, economical status, health condition, leisure activity, communication, consumption activity) on the element life satisfaction(self-respect, personal relations, emotional condition, physical health, consume activity) of life for the aged. For the study, I collected 280 samples from people of 60 year-old adults who reside of in Gyeonggi-do. I used factor analysis, reliability analysis, multi-regression, t-test, ANOVA with SPSS 18.0. The results are as follows. First, satisfaction about aged population sociological character level of significance were difference in factors except gender, statistically. Second, daily living factors and element satisfaction between analysis positive relation. Third, Aged of daily living factors effect to element satisfaction, social support and leisure activity effect to self-respect, are social support, health condition, leisure activity effect to personal relations and physical health satisfaction. and communication effect to Emotional condition and economical status, communication and consume activity effect to economical living satisfaction. 본 연구는 노인의 일상생활요인(사회적지지, 경제상태, 건강상태, 여가활동, 의사소통, 소비활동)이 영역별 삶의 만족도(자아존중, 대인관계, 정서상태, 신체건강, 경제생활) 에 미치는 영향을 파악하고자 하였다. 연구 대상은 경기도 지역에 거주하는 60세 이상 노인 280명을 대상으로 하였다. 자료 분석은 SPSS 18.0 프로그램을 이용하여 빈도분석, 요인분석, 신뢰도분석 및 t-test, ANOVA, 분산분석 등을 하였다. 연구결과는 첫째, 노인의 인구사회학적 특성에 따른 삶의 만족도 차이는 성별을 제외한 분야에서 통계적으로 유의한 차이가 나타났다. 둘째, 일상생활요인과 영역별 삶의 만족도 간에는 정적 상관관계가 있는 것으로 분석되었다. 셋째, 노인의 일상생활요인이 영역별 삶의 만족도에 미치는 영향은 자아존중 만족도는 사회적지지와 여가활동이 영향요인으로, 대인관계 만족도와 신체건강만족도의 경우 사회적지지, 여가활동 및 건강상태가 영향요인이었고, 정서상태만족도는 의사소통, 경제생활 만족도는 경제상태, 의사소통 및 소비활동이 영향요인인 것으로 분석되었다.